Information Literacy in France and Japan - Sunaga, Kazuyuki (Qualitative and Quantitative Methods in Libraries; Vol 6 No 2 (2017): June 2017 Issue, 2019)
The Brevet Informatique et Internet (B2i) is a certificate and the method is a checklist to verify pupil’s information skills in France. The B2i consists of five domains; learning environment, attitude responsible, information processing, utilization of information and communication. The ministry of Education in France has conducted the B2i for all pupils. The B2i is intended for pupils in every final school year of elementary school, middle school and senior high school. The model of the Information Moral Teaching model curriculum (IMT) in Japan resembles the B2i. The model is composed of five domains as well as the B2i, but that emphasizes the information ethic and adverse effects on the health rather than the utilisation of social network service.